2017
DOI: 10.1002/adfm.201702689
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Topography Mediates Filopodial Extension and Morphology of Cells on Stiff Materials

Abstract: Figure 5. C) Dependence of the average filopodial extension velocity on the adhesion strength γ and surface roughness. α here represents the shrinking factor with α = 1 corresponding to the initial MCD topography. Error bar here indicates the standard deviation of simulation results from eight different MCD topographies. For comparison, the measured speeds of growing filopodia on MCD and NCD substrates are also given by the purple and blue cross markers (assuming γ = 9 × 10 −5 J m −2 ), respectively.The above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
(56 reference statements)
2
18
0
Order By: Relevance
“…The deposition of microcapsules led to an obvious increase in surface roughness, indicating a desirable topography to enhance the cell-material interactions for clinical applications. 11,47,48…”
Section: Resultsmentioning
confidence: 99%
“…The deposition of microcapsules led to an obvious increase in surface roughness, indicating a desirable topography to enhance the cell-material interactions for clinical applications. 11,47,48…”
Section: Resultsmentioning
confidence: 99%
“…[11] Further atomic force microscopy (AFM) analyses indicated that, in contrast to the smooth PL layer ( Figure S1e, Supporting Information), the incorporation of CNFs led to an obvious increase in surface roughness from 2-5 to 10-50 nm (Figure 1f), showing a topography that can enhance cell-material interactions for clinical applications. [34,35] Our unique pinecone-inspired design allowed the microcages to possess remarkable loading capability with drug size >100 nm, more than ten times higher than that of the control polymer capsules (Figure 1g). Meanwhile, both their mechanical property and hydrophilicity were greatly enhanced compared to the control capsules (>150% improved compressive strength and from hydrophilic to superhydrophilic; Figure 1h,i).…”
Section: Pinecone-inspired Design For Microcagesmentioning
confidence: 99%
“…35 Disordered topography, as is the case for most biological tissue and almost all clinically accepted biomaterials, is reported to highly affect the morphology of osteoblast cells. 36 Figures 5 and 6 shows the OM and SEM micrographs representing the morphology of Saos-2 cells cultured on coated and uncoated samples after 3 days in culture. The cells cultured on the coated surface represent a rather flat morphology whereas the cultures on uncoated samples represent a more rounded configuration.…”
Section: Resultsmentioning
confidence: 99%